Is moderate-intensity interval training more tolerable than high-intensity interval training in adults with obesity? - Maaloul, Rami; Ben Dhia, Imen; Marzougui, Houssem; Turki, Mouna; Kacem, Faten; Makhlouf, Rihab; Amar, Mohamed; Kallel, Choumous; Driss, Tarak; Elleuch, Mohamed; Ayadi, Fatma; Ghroubi, Sameh; et al. (Biology of Sport, 2023)
Interval training (IT) has been shown to be a time-effective alternative to traditional training programmes in the management of obesity. Nevertheless, studies comparing the effects of different IT intensities on inflammation, muscle and liver damage, and perceptual responses in people with obesity are relatively scarce. This study aimed to compare the acute effects of two different IT protocols matched by the mean load and duration on biochemical and perceptual responses in sedentary adults with obesity. Twenty-two volunteers (age = 33.40±10.01 years, BMI = 38.29±7.09 kg/m²) were randomized to perform two conditions: moderate intensity IT (MIIT) 5×3 min (70% of peak power output (PPO))/2 min (45%PPO) and high-intensity IT (HIIT) 8×1 min (90%PPO)/2 min (45%PPO). Blood samples were drawn before and after exercise for biochemical and haematological measurements. Rating of perceived exertion (RPE) was assessed during and after exercise. Perceptual pain was evaluated before, throughout and after exercise. C-reactive protein, white blood cells and neutrophils increased only after HIIT (p < 0.001, for all). Aspartate aminotransferase, alanine aminotransferase, creatine kinase and lactate dehydrogenase increased in both HIIT and MIIT (p < 0.001, for all), without any difference between sessions. HIIT induced a greater increase of blood lactate compared to MIIT (p < 0.05). Pain and RPE scores were higher during HIIT vs. MIIT (p < 0.001 and p < 0.01, respectively). MIIT induced fewer immune system perturbations and less muscle pain and was perceived as more tolerable compared to HIIT session. Therefore, MIIT could be used as a first step to promote body adaptations before starting a HIIT programme in sedentary people with obesity.